Synthesis, Characterization, Theoretical Crystal Structure, and Antibacterial Activities of Some Transition Metal Complexes of the Thiosemicarbazone (Z)-2-(pyrrolidin-2-ylidene)hydrazinecarbothioamide - Ahmed A. Al-Amiery; Yasmien K. Al-Majedy; Haziem Abdulreazak; Hussain Abood (Bioinorganic Chemistry and Applications)
Problem Statement. In Iraq like most third world countries, attempts discovered new antibiotic drugs derived from thiosemicarbazide and its metal complexes and developed the branch of applied in organic chemistry. Approach. New (Z)-2-(pyrrolidin-2-ylidene)hydrazinecarbothioamide (L) was synthesized in a good yield by the reaction of pyrrolidone with thiosemicarbazide. Co(II), Ni(II), and Cu(II) complexes of (L) were prepared and characterized by FT-IR, UV/visible spectra, 1HNMR, and CHN analyses. Moreover, charge, bond length, bond angle, twist angle, heat of formation, and steric energy were calculated by using of the ChemOffice program, and the DFT calculations for the complexes were done. The free ligand and its metal complexes were tested in vitro against several microorganisms (Staphylococcus aurous, E. coli, Proteus vulgaris, Pseudomonas, and Klebsiella pneumoniae) to assess their antimicrobial properties. Results. The study shows that these complexes have octahedral geometry; in addition, it has high activity against tested bacteria. Conclusion/Recommendations. Based on the reported results, it may be concluded that ligand acts as bidentate, neutral ligand, coordinating through one of the nitrogen and sulfur atoms.